Dirty Bertie Smash - MacDonald, Alan.; Roberts, David (London : Stripes Publishing, 2014)
Calling all Dirty Bertie fans! Dirty Bertie - the boy with nose-pickingly disgusting habits - is back for another helping of comic chaos! With ever-increasing madcap schemes and crazy capers, Bertie continues to delight his legions of fans who revel in his revolting ways.
3-6.
Turkish.
Keywords: Behavior -- Fiction